Childfree Dalam Pandangan Katolik: Pandangan Penganut, Pemuka Agama, dan Umat Gereja - Kristy, Bella (Emik, 2024)
The term childfree is used to refer to people or couples who choose not having children. Childfree is considered violating Catholic marriage vow and becomes controversy. Despite its controversy, childfree becomes more common. This article deals with childfree in Catholic teachings from the view of childfree adherents, religious leaders, and church people. This qualitative research was conducted in Makassar. There are 13 informants who get involved in this study, consisting of six childfree adherents, a priest, two fraters and four Catholics. Data was collected using in-depth interview and observation. Childfree among Catholic couples raises oppositional responses, between those who agree and those who disagree. The Catholic Church teaches that procreation is the main purpose of marriage, while each individual is free to choose not to have children (childfree). Procreation is not only seen as a biological act, but also as a spiritual act that consummates marriage and is part of God's plan. Children are not only considered descendants, but also "gift from God." The reasons why Catholic couples choose to be childfree are the trauma of miscarriage, fear of childcare, the desire to enjoy being together as a couple, and not wanting to be bothered. Although the choice to be childfree is a personal right, this is contrary to the teachings of the Catholic Church. The childfree option is quite disturbing when viewed from the perspective of Catholic teachings. However, if a Catholic couple has made a choice, they are expected to balance it with religious service activities. This means that even though the childfree choice is contrary to Catholic teachings, they are expected to get closer to God to balance between the choice and the service. Catholic religious leaders expressed their concern about the increasingly widespread childfree phenomenon. According to them, childfree goes against Catholic religious teachings regarding marriage and procreation. Catholics also have different views regarding rejecting childfree because they consider it a rejection of God's will and ignoring the purpose of marriage. Accepting a partner's choice to be childfree is simply out of respect for each partner's personal decision as an individual right.